Silicon, a quasi-essential element Availability in soil, fertilizer regime, optimum dosage, and uptake in plants - Thakral, Vandana (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.